2020
DOI: 10.1088/2053-1591/ab6e2c
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation behavior of as-cast Mg-3Zn-1Ca-0.5 Sr alloy

Abstract: Recent advancements in bone implant materials have led to the development of various alloys. In this study, the degradation behavior of the as-cast Mg-3 wt% Zn-1 wt% Ca-0.5 wt% Sr alloy in vitro was investigated using x-ray diffraction (XRD), scanning Kelvin probe force microscopy (SKPFM), and scanning electron microscopy (SEM). Our results demonstrated that the alloy microstructure was composed of α-Mg, a Ca 2 Mg 6 Zn 3 phase, and a Mg 17 Sr 2 phase. The Ca 2 Mg 6 Zn 3 phase, which had the smallest absolute p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It has been reported that the glass-forming ability (GFA) of the alloys can be improved by the addition of Sr to the Mg-Zn-Ca alloys, [1] and the corrosion resistance of Mg alloys has been improved by the addition of low content Sr [13][14][15]. As a natural component in the human body, strontium (Sr) fully fulfils the requirements of biocompatibility, which can enhance the proliferation of osteoblasts, inhibit osteoporosis, increase bone density and strength, and its degradation products can be metabolised without causing any harm to the human body [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the glass-forming ability (GFA) of the alloys can be improved by the addition of Sr to the Mg-Zn-Ca alloys, [1] and the corrosion resistance of Mg alloys has been improved by the addition of low content Sr [13][14][15]. As a natural component in the human body, strontium (Sr) fully fulfils the requirements of biocompatibility, which can enhance the proliferation of osteoblasts, inhibit osteoporosis, increase bone density and strength, and its degradation products can be metabolised without causing any harm to the human body [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%